2008
DOI: 10.4137/cmbd.s507
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Drug-Induced mRNA in Human Whole Blood ex vivo

Abstract: Apoptosis was induced in heparinized human whole blood by 3 different ways (radiation, bleomycin, or etoposide), and various mRNA were quantifi ed using the method we reported (Clin. Chem. 2006; 52:634-642). We found that cyclin-dependent kinase inhibitor 1A (p21) and p53 upregulated modulator of apoptosis (PUMA) were the most sensitive and universal mRNA markers of apoptosis in leukocytes. In order to defi ne positive and negative responses, a synthetic RNA was spiked into the lysis buffer and the fold increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…[11][12][13] In brief, 50 L of blood sample was applied to 96-well filter plates in order to trap leukocytes. Sixty microliters of lysis buffer containing a cocktail of specific reverse primers was applied to the filter plates, and the resultant cell lysates were transferred to oligo(dT)-immobilized microplates (GenePlate, RNAture, Irvine, CA) 17 for poly(A) ϩ mRNA purification.…”
Section: Mrna Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] In brief, 50 L of blood sample was applied to 96-well filter plates in order to trap leukocytes. Sixty microliters of lysis buffer containing a cocktail of specific reverse primers was applied to the filter plates, and the resultant cell lysates were transferred to oligo(dT)-immobilized microplates (GenePlate, RNAture, Irvine, CA) 17 for poly(A) ϩ mRNA purification.…”
Section: Mrna Quantificationmentioning
confidence: 99%
“…In the first half of this study, we developed a unique system to assess the overall function of the Fc␥R and the TCR under physiological ex vivo conditions using an assay system we previously described. [11][12][13] We then used this technology to assess the functions of the Fc␥R and the TCR in inflammatory bowel diseases (IBD) 14 because leukocytes play a role of pathogenesis of IBD by migrating to the disease site. Although the primary disease site is small intestine and colon in IBD, this study specifically focused on the functions of the Fc␥R and the TCR on peripheral-blood leukocytes as surrogate markers of IBD.…”
mentioning
confidence: 99%
“…Differences in Cycle threshold (C t ) between the target and control mRNA (β actin) (ΔC t ) were used to quantify the relative amount of each target, calculated as 2 ÀΔC t . Primers used for gene expression assays have been previously described [25][26][27][28].…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…We recently found that mRNAs for p21 and PUMA 4 (p53 up-regulated modulator of apoptosis) were the most predictive mRNA markers of leukocyte apoptosis (5 ) and that the induction of these mRNAs was detectable in human whole blood within 1-4 h of drug incubation (5 ). p21 is an inhibitor of cyclindependent kinase (6 ), and increased p21 production consequently causes cell cycle arrest (7 ).…”
Section: © 2008 American Association For Clinical Chemistrymentioning
confidence: 99%
“…6) also showed weak p21 mRNA responses to ACR, but these ACR responses corresponded to CRs. Because high doses of AraC and DNR failed to induce p21 and PUMA mRNA responses in case 2, we also analyzed other BAX family mRNAs, as is described in our previous report (5 ). This study demonstrated that high doses of AraC, DNR, and MIT did not induce apoptosis-related mRNAs (GADD, SUMO, Apaf1, Bfl1, BclII, Bim, Bik, Bid, Bad, Bcl-xs, Bak, and Bax) (data not shown).…”
Section: Case Studiesmentioning
confidence: 99%